Turbulent flows in channels and pipes - Chau, Khanh Le (Vietnam Journal of Mechanics, 2007)
A variational principle for channel and pipe flows of incompressible viscous fluid is proposed. For low Reynolds numbers this variational principle reduces to the principle of minimum dissipation. For high Reynolds numbers it enables one to calculate the velocity profiles and the corresponding friction factors with reasonably good accuracy.